Analysis of the Relationship between Physical Fitness Levels and Sport Values of High School Futsal Extracurricular Students - Fauzan Hana Fadhlurrahman; Nuryadi; Helmy Firmansyah (Universitas Negeri Semarang, 2026)
Physical fitness is an important element in achieving maximum athletic performance, while sport values reflect the attitudes and ethics that every athlete should possess. This study aims to identify the level of physical fitness and sport values among athletes participating in futsal extracurricular activities at senior high schools and to determine whether there is a relationship between physical fitness and sport values. This study used a quantitative descriptive method with a sample of 49 futsal extracurricular athletes at a high school in Cimahi City. Data were obtained through two stages, namely the TKSI (Indonesian Student Fitness Level) test and a questionnaire. The questionnaire was in the form of YSVQ-2 (Youth Sport Values Questionnaire) to measure the extent of sports values possessed, and the TKSI test consisted of 6 tests (hand and eye coordination, vertical jump, t-test, hand touch reaction test, dipping test, and beep test) to determine the level of physical fitness of the students. The results of the study showed that the average physical fitness score was 66% and the sport values score was 51%. In addition, the correlation test results showed that there was no correlation between physical fitness and sport values (sig=0.275; r=0.119). This was due to several factors, such as the fact that assessments in sports tend to be subjective and focus more on technical and tactical abilities, as well as environmental factors such as the availability of sports facilities. Weather conditions and social support can influence participation in physical activity. The impact on sports values and physical fitness can vary depending on these conditions. Therefore, values in sports cannot be used as an accurate indicator to assess a person's level of physical fitness.